Surgical technique and implant design affect abduction kinematics and functional outcomes after reverse shoulder arthroplasty - Kane, Gillian; LeVasseur, Clarissa; Rai, Ajinkya; Munsch, Maria; Gabrielli, Alexandra S.; Como, Christopher J.; Hughes, Jonathan D.; Anderst, William; Lin, Albert (Medical engineering & physics, 2025)
•Kinematics after reverse shoulder arthroplasty were measured using biplane radiography.•Neck shaft angle, glenosphere size, and retroversion were associated with outcomes.•In vivo data is needed to validate biomechanical and simulation studies. The purpose of this study was to identify surgical techniques and implant geometries that influence in-vivo kinematics, functional outcomes, and clinical outcomes after reverse shoulder arthroplasty (RSA). Synchronized biplane radiographs imaged the operated shoulder during scapular plane abduction in 35 patients who received RSA within the past 2.5 ± 1.2 yrs. Shoulder kinematics and arthrokinematics (contact paths) were determined by matching subject-specific CT-based bone-plus-implant models to the radiographs using a validated tracking technique. Torque and total work done during abduction were measured using an isokinetic dynamometer. Implant characteristics and surgical techniques that were associated with kinematics/arthrokinematics, strength, or patient-reported outcomes were identified using multiple linear regression. Neck shaft angle, glenosphere size, and retroversion were associated with in-vivo kinematics and functional outcomes during abduction after RSA. These findings improve our understanding of how implant design and surgical technique impact kinematics and functional outcomes after RSA. The results highlight the necessity of in vivo data to validate cadaver-based research and computer simulations of joint function after RSA, emphasizing that those models do not account for the dynamic healing process and neuromuscular adaptations that occur after surgery.